2021
DOI: 10.3389/fpsyg.2021.753061
|View full text |Cite
|
Sign up to set email alerts
|

How Does Job Insecurity Affect Workplace Harassment? The Interaction Effect of Hypercompetitive Attitude, Coworker Impression Management, and Leader Narcissism

Abstract: With concerns that artificial intelligence may replace existing jobs, job insecurity is becoming more prevalent. In-depth study of how job insecurity affects our society has become an important research topic. This study investigates the internal mechanisms through which such job insecurity influences workplace harassment. Based on the theories of psychological contract breach and the conservation of resources, this study proposes an indirect effect of job insecurity and a three-way moderation effect of hyperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…The results show that there is a direct relationship between psychosocial risks and the perception of WPV. Thus, coinciding with other authors (Bentley et al, 2014;Figueiredo-Ferraz et al, 2012;Hirigoyen, 2001;Song, 2021;Zahlquist et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results show that there is a direct relationship between psychosocial risks and the perception of WPV. Thus, coinciding with other authors (Bentley et al, 2014;Figueiredo-Ferraz et al, 2012;Hirigoyen, 2001;Song, 2021;Zahlquist et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies show that in organizations where job insecurity prevails, situations of harassment can appear more easily due to the presence of hypercompetitive attitudes, the control of the impressions that other colleagues have of us and the narcissistic leadership style (Palma-Contreras & Ansoleaga, 2020). According to Song (2021), there is a causal relationship between psychological anxiety about losing a job and the intention of bullying (Song, 2021).…”
Section: Psychosocial Risk Factors and Workplace Violencementioning
confidence: 99%
“…This implies that abusive supervision is a low base rate phenomenon [ 35 ]. Our results further revealed relative lower impression management motivation scores than other academic studies [ 17 , 18 ], and speak up-related climate scores were slightly higher than previous findings [ 36 ].This disparity may arise from variances in the diverse occupational backgrounds and geographical origins within the study population [ 17 , 18 , 37 ]. In addition, our results showed lower nurses’ withholding voice about patient safety scores than other academic studies [ 5 , 38 ].…”
Section: Discussionsupporting
confidence: 57%
“…Impression management motivation refers to ‘the extent to which individuals are motivated to control the perception others have of them’ [ 16 ]. This motivation is contingent on the context, and individuals who display motivation for impression management are influenced by factors such as leadership styles and the external climates [ 17 , 18 ]. Previous studies in China have demonstrated that the impression management motivation could serve as a mediating factor between leadership behaviour and the voice behaviour [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%